KEPUASAN PETANI TERHADAP PERAN PENYULUH PERTANIAN DALAM PENYULUHAN TANAMAN PADI SAWAH DI DESA KASIMPA JAYA KECAMATAN TIWORO SELATAN KABUPATEN MUNA BARAT - Riadi, Rian; Mappasomba, Musadar; Salahuddin, Salahuddin; Dima, Darsilan (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2025)
The efficacy of agricultural development is predominantly contingent upon the strategic function of agricultural extension workers in enhancing farmers' knowledge, skills, and innovation. Farmers' satisfaction and favorable response to the performance of extension workers are pivotal factors in achieving dynamic, innovative, and competitive agriculture. The objective of this study is to ascertain the level of satisfaction among farmers in relation to the role of agricultural extension workers in rice field extension in Kasimpa Jaya Village, South Tiworo District, West Muna Regency. The research population comprised all 94 rice farmers residing in Kasimpa Jaya Village. The sample size was determined using the Slovin formula with an error rate of 10%, resulting in a sample size of 20 people. The sampling method employed was simple random sampling. The data were collected through a combination of interviews, documentation, and surveys administered via questionnaires. The research variables of interest were farmer satisfaction and the role of agricultural extension workers. The collected data were then subjected to a descriptive analysis. The results indicated that farmer satisfaction with the role of agricultural extension workers in Kasimpa Jaya Village was moderate, with high ratings for product quality and service, while the public emotional aspect was moderate. The role of agricultural extension workers is moderate, and their roles in education, motivation, facilitation, and counseling still need to be improved. Agricultural extension workers have played a fairly effective role in providing education and technical services; however, they have not been optimal in building emotional closeness and facilitating the needs of farmers as a whole.